2020
DOI: 10.1101/2020.10.22.351445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transient light-activated gene expression in Chinese hamster ovary cells

Abstract: Background: Chinese hamster ovary (CHO) cells are widely used for industrial production of biopharmaceuticals. Many genetic, chemical, and environmental approaches have been developed to modulate cellular pathways to improve titers. However, these methods are often irreversible or have off-target effects. Development of techniques which are precise, tunable, and reversible will facilitate temporal regulation of target pathways to maximize titers. In this study, we investigate the use of optogenetics in CHO cel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The T7 promoter in pET28a was replaced by P32, hence reducing the cost of the whole process. At the same time, according to literature, P32 promoter is conducive to improving production (Minami and Shah, 2021 ). The fermentation experiment showed that K.P .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The T7 promoter in pET28a was replaced by P32, hence reducing the cost of the whole process. At the same time, according to literature, P32 promoter is conducive to improving production (Minami and Shah, 2021 ). The fermentation experiment showed that K.P .…”
Section: Discussionmentioning
confidence: 94%
“…Thus, a new gene regulatory tool was developed (Prykhozhij et al ., 2017 ; Saifaldeen et al ., 2021 ). CRISPR‐dCas9 has advantages over common genome regulatory techniques, such as species restrictions, multiple gene regulatory methods, high gene modification rate and simple simultaneous regulation of multiple genes (Deaner et al ., 2018 ; Schwartz et al ., 2018 ; Velegzhaninov et al ., 2020 ; Minami and Shah, 2021 ).…”
Section: Introductionmentioning
confidence: 99%